2023
DOI: 10.3892/ol.2023.13804
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of involucrasin A on colorectal cancer cells by modulating the Akt/MDM2/p53 pathway

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer mortality worldwide; however, there is still a lack of effective clinical anti-CRC agents. Naturally-occurring compounds have been considered a potentially valuable source of new antitumorigenic agents. Involucrasin A, a novel natural molecule, was isolated from Shuteria involucrata (Wall.) Wight & Arn by our team. In the present study, the anticancer activity of involucrasin A in HCT-116 CRC cells was evaluated. Firstly, the anti-proliferative effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Both compounds exhibited significant inhibitory effects on CRC cells, although their specific inhibitory mechanisms differed. Involucrasin A induced cell death in CRC cells by modulating the Akt/MDM2/P53 pathway [8], while involucrasin B, as investigated in this study, suppressed CRC cell proliferation by regulating the TGFβ/SMAD2-3-4 pathway. Comparative and repetitive analysis of the nuclear magnetic resonance spectra revealed that the ~1H and ~(13) C NMR spectra of involucrasin B were highly similar to those of involucrasin A, except for the absence of the methoxy signal in involucrasin B [13].…”
Section: Discussionmentioning
confidence: 56%
See 4 more Smart Citations
“…Both compounds exhibited significant inhibitory effects on CRC cells, although their specific inhibitory mechanisms differed. Involucrasin A induced cell death in CRC cells by modulating the Akt/MDM2/P53 pathway [8], while involucrasin B, as investigated in this study, suppressed CRC cell proliferation by regulating the TGFβ/SMAD2-3-4 pathway. Comparative and repetitive analysis of the nuclear magnetic resonance spectra revealed that the ~1H and ~(13) C NMR spectra of involucrasin B were highly similar to those of involucrasin A, except for the absence of the methoxy signal in involucrasin B [13].…”
Section: Discussionmentioning
confidence: 56%
“…However, despite treatment advancements, advanced CRC still exhibits high mortality rates [7]. Studies suggest that while screening has reduced early morbidity, there has been an increase in the occurrence and fatality of advanced CRC in recent years [6,8]. The chemotherapy limitations in current CRC management include systemic toxicity, low tumor specificity, and acquired drug resistance [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations